"N‐π‐N" Type Oligomeric Acceptor Achieves an OPV Efficiency of 18.19% with Low Energy Loss and Excellent Stability. Issue 23 (16th June 2022) - Zhang, Lili; Zhang, Ziqi; Deng, Dan; Zhou, Huiqiong; Zhang, Jianqi; Wei, Zhixiang
Abstract: A novel "N‐ π ‐N" type oligomeric acceptor of 2BTP‐2F‐T, constructed by two small non‐fullerene acceptor (NFA) units linked with a thiophene π bridge is reported. The 2BTP‐2F‐T not only combines the advantages of small NFA and polymeric acceptors (PYF‐T‐ o ) with similar units but also exhibits superior characteristics of high absorption coefficient and high electron moblity( µ e) ) with less dependence on molecular packing. Using PM6 as the donor, a remarkable efficiency of 18.19% is obtained with an open circuit ( V oc ) of 0.911 V, short current circuit ( J sc ) of 25.50 mA cm −2, and fill factor (FF) of 78.3%, which is much better than that of the corresponding monomer (16.54%) and PYF‐T‐ o (15.8%) based devices. The much‐improved efficiency results from two aspects: 1) an enhanced FF due to the largely improved µ e and well‐controlled morphology ; 2) a higher value of ( J sc × V oc ) due to its higher absorption coefficient and efficient charge generation at a similar low energy loss. Furthermore, the PM6/2BTP‐2F‐T device possesses the longest T80 lifetime to light‐soaking and comparable high thermal stability with PM6/PYF‐T‐ o . The results indicate that the "N‐ π ‐N" type oligomeric acceptor has a great application prospect due to its superior high efficiency and improved stability in organic solar cells. Abstract : A novel oligomeric acceptor 2BTP‐2F‐T, constructed by linking two non‐fullerene acceptors with thiophene, is reported. It exhibits superior characteristics over its monomer and polymer, including higher absorption coefficient and electron mobility in pristine materials, and welltuned morphology in PM6 blends, pushing an attain of efficiency of 18.19% with improved fill factor and short circuit current under similar energy loss.